Metaforyczne ożywianie miasta. Praktyka na pograniczu nauki i sztuki - Filanowski, Błażej (Strategie komunikacyjne i procesy twórcze, 2022)
The paper analyzes the sources of the modern metaphor of revival of the city, finding conections with of two concepts taken from the biological sciences: circulation and metabolism. The author describes how this understanding of the city as an organism influenced two important architectural and artistic concepts: the Modern City and the Situacionist City. Assuming contemporary relevance of both concepts, the paper develops usus of the word "revival" as a participatory process in the crisis-define area in the contemporary discourse on a field of administrations and research in Poland. The author compares the revival practice with the analyzed artistic concepts and their contemporary reception, noting that every action is unique, and its effectiveness it's difficult to predict.